The regulatory role of gibberellin related genes DKGA2ox1 and MIR171f_3 in persimmon dwarfism. (September 2021) - Dong, Yuhan; Ye, Xialin; Xiong, Aisheng; Zhu, Ning; Jiang, Luping; Qu, Shenchun
Highlights: Persimmon transgenic system was successfully established. D. kaki Thunb. could be used as an interstock to induce dwarfing in grafted scions. Dwarf character was better when interstock lengths were between 20 and 25 cm. Key genes related to dwarfing persimmon were screened and verified. DKGA2ox1 and MIR171f_3 regulate persimmon dwarfism by affecting GA content in scion. Abstract: 'Nantongxiaofangshi' ( Diospyros kaki Thunb., D. kaki Thunb.) is a local cultivar of persimmon with dwarf-like traits in Jiangsu, China. Closely spaced planting afforded by dwarfism is usually one of the most important ways to promote fruit cultivation and production. However, the understanding of dwarfism in D. kaki Thunb. is very limited at the molecular level, which hinders the further increase of the fruit production. In this work, a persimmon transgenic system was successfully established, and the field experiments of grafting phenotype were carried out. The results showed that D. kaki Thunb. could be used as an interstock to induce dwarfing in grafted scions, and the dwarf character was better when interstock lengths were between 20 and 25 cm. Furthermore, the key genes related to dwarfism in D. kaki Thunb. were screened and verified, and subsequently, the regulatory role of related genes in persimmon dwarfism was figured out. It was found that the gene encoding gibberellin 2-oxidase-1 ( DkGA2ox1 ) involved in GA biosynthesis was associated with the dwarfing in D. kaki Thunb. Overexpression of DkGA2ox1 in Diospyros lotus resulted in a typical dwarf phenotype. Meanwhile, the microRNA data showed that the miR171f_3 demonstrated the active involvement in GA pathway response in persimmon dwarfism. DkGA2ox1 and MIR171f_3, as two highly expressed genes in D. kaki Thunb. interstock, could be used as stimulus signals to affect the content of GA in scion, however, the specific transmission mechanism still needs to be further explored. Ultimately, the bioactive GA level was decreased, resulting in the scion dwarfism.